Modern Marketing Strategy Development for Community Pharmacy Business - Wattanathum, Krit; Fuangchan, Anjana (Journal of Business, Innovation and Sustainability (JBIS), 2023)
Retail pharmacy is a highly competitive industry and modern consumer behaviors have changed. This research aimed to develop the modern marketing strategy for retail pharmacy by using modified Delphi’s technique. A panel of experts included 13 qualified individuals who possess relevant expertise or experience in the field of retail pharmacy, pharmacist’s influencer, or marketing specialist. A semi-structured questionnaire was initially used, and a questionnaire developed from the first round of interview findings was subsequently applied. The six domains of modern marketing strategy were proposed, including personalized marketing, digital marketing and the application of technology, service quality, added value of pharmacist’s activities, marketing mix, and environmental issues. PROMPTS-DATE is an acronym representing this strategy that could be applied to suit the current pharmacy situation.